2006
DOI: 10.1136/bmj.38863.638194.ae
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of driving while sleepy and road traffic accidents: prospective study in GAZEL cohort

Abstract: Objectives To examine the association between self assessed driving while sleepy and the risk of serious road traffic accidents (RTAs). Design Prospective cohort study. Setting France. Participants 13 299 of the 19 894 living members of the GAZEL cohort, workers and recent retirees of a French national utility company followed up since 1989. Main outcome measures Frequency of driving while sleepy in the previous 12 months, reported in 2001; rate ratios for serious RTAs in 2001-3, estimated by using generalised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 19 publications
5
46
1
Order By: Relevance
“…There are elements, however, pointing to a fair reliability of self-reports on behavior and attitudes in our survey. First, significant trends between the risk of road traffic accidents and self-reported well-known behavior were found in the GAZEL cohort (speeding, driving while intoxicated, sleepy driving, and phone use while driving) (22,38). Second, we observed a fair consistency between responses to the same questions in 2001 and in 2004, as shown by weighted kappa coefficients between behavioral self-reports (0.45 for sleepy driving, 0.40 for phone use while driving, and 0.51 for driving while intoxicated) and by intraclass correlations between reported speeds (0.49 for built-up areas, 0.42 for rural roads, and 0.61 for highways).…”
Section: Discussionmentioning
confidence: 99%
“…There are elements, however, pointing to a fair reliability of self-reports on behavior and attitudes in our survey. First, significant trends between the risk of road traffic accidents and self-reported well-known behavior were found in the GAZEL cohort (speeding, driving while intoxicated, sleepy driving, and phone use while driving) (22,38). Second, we observed a fair consistency between responses to the same questions in 2001 and in 2004, as shown by weighted kappa coefficients between behavioral self-reports (0.45 for sleepy driving, 0.40 for phone use while driving, and 0.51 for driving while intoxicated) and by intraclass correlations between reported speeds (0.49 for built-up areas, 0.42 for rural roads, and 0.61 for highways).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that individuals experiencing sleep deprivation and fatigue pose serious health and safety risks to others and themselves because of cognitive and motor impairments and mood disturbance. 29,30 Even modest sleep restriction (a reduction from 8 to 6 hours per night for one week) in young, healthy, normal sleepers leads to significant sleepiness, psychomotor impairment, and increased secretions of proinflammatory cytokines. 31 A large majority of nurses are female, 32 and shift work adversely affects females more than males, making this target group especially vulnerable to the impact of insufficient or disturbed sleep.…”
Section: Health and Safetymentioning
confidence: 99%
“…In a study by Powell and colleagues (2001), sleep deprived drivers were found to perform as poorly as drivers under the influence of alcohol in a closed-course driving test and displayed little awareness of their driving errors. These associations are further corroborated by findings from epidemiological crash studies, which identify lack of sleep as a significant contributor in 20% of all traffic accidents (Howard et al, 2004;Nabi et al, 2006;Sagaspe et al, 2010). For instance, in a retrospective analysis of 4871 crash reports for drivers of all ages in Japan, Abe and colleagues (2010) found that short sleep duration (<6h) the previous night was significantly associated with both rear-end collisions and single-car accidents.…”
Section: Introductionmentioning
confidence: 79%